Green Economy Indicators and Determinants in South Sulawesi Province - Rahayu, A. Anna; Tikson, Deddy T.; Yunus, Muhammad (KnE Social Sciences, 2025)
The aim of this study was to measure indicators and determinants of the level of green economic development in South Sulawesi Province based on driving factors, status, impact or influence, and models of the green economy regionally. This measurement was carried out to evaluate and develop the green economy using a quantitative approach to the DPSIR conceptual model with the multicriteria decision-making analysis method (MCDMA), which is widely used to assess the diversity of socio-economic phenomena. This makes it possible to rank regions and progress in green economic development in South Sulawesi Province. The results of the study found that all regions in South Sulawesi Province experienced progress in terms of green economic growth, but from several indicators, there were still regions that experienced a slowdown in several sectors.